2018
DOI: 10.1371/journal.pone.0192596
|View full text |Cite
|
Sign up to set email alerts
|

Low free 25-hydroxyvitamin D and high vitamin D binding protein and parathyroid hormone in obese Caucasians. A complex association with bone?

Abstract: BackgroundStudies have shown altered vitamin D metabolism in obesity. We assessed differences between obese and normal-weight subjects in total, free, and bioavailable 25-hydroxyvitamin D (25(OH)D, 25(OH)DFree, and 25(OH)DBio, respectively), vitamin D binding protein (DBP), parathyroid hormone (PTH) and bone traits.Methods595 37-47-year-old healthy Finnish men and women stratified by BMI were examined in this cross-sectional study. Background characteristic and intakes of vitamin D and calcium were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
1
18
1
Order By: Relevance
“…Both opioid [36] and endocannabinoid systems [37] are known to play a role in the regulation of food intake and thermogenesis and the metabolic alterations associated with obesity. Lower 25(OH)D levels observed in postmenopausal women with higher VAT levels are consistent with findings in numerous studies [25,[38][39][40][41]. Several reasons for lower 25(OH)D levels in obese individuals have been postulated, including sequestration of vitamin D by adipose tissue making it less bioavailable [39] or lower cutaneous synthesis with age [42].…”
Section: Discussionsupporting
confidence: 87%
“…Both opioid [36] and endocannabinoid systems [37] are known to play a role in the regulation of food intake and thermogenesis and the metabolic alterations associated with obesity. Lower 25(OH)D levels observed in postmenopausal women with higher VAT levels are consistent with findings in numerous studies [25,[38][39][40][41]. Several reasons for lower 25(OH)D levels in obese individuals have been postulated, including sequestration of vitamin D by adipose tissue making it less bioavailable [39] or lower cutaneous synthesis with age [42].…”
Section: Discussionsupporting
confidence: 87%
“…Other possible explanations for the varying associations between the levels of vitamin D and HbA1c include vitamin D receptor gene polymorphism, the interaction of vitamin D with the insulin-like growth factor system 13 and the influence of other hormones 40 . Alterations in free vitamin D levels, particularly in obese individuals, should also be considered 41 . How the latter influences the effects of vitamin D in tissues remains to be firmly established [41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in free vitamin D levels, particularly in obese individuals, should also be considered 41 . How the latter influences the effects of vitamin D in tissues remains to be firmly established [41][42][43] . Not all risk factors for prediabetes/diabetes mellitus influence disease pathogenesis equally.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have reported that obesity disfavors an adequate 25(OH)D concentration [ 36 38 ], the association between obesity and other biomarkers of the vitamin D status was poorly investigated. Higher DBP concentrations in obese individuals have been previously reported [ 39 , 40 ]. It was postulated that the higher interleukin-6 frequently observed in obesity could be behind the higher DBP concentrations among obese individuals [ 39 ].…”
Section: Discussionmentioning
confidence: 83%